2004
DOI: 10.1080/02786820490494043
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Test of a Sampling Method for Characterization of Combustion Aerosols at High Temperatures

Abstract: The objective of this study was to design and experimentally examine a sampling method for high-temperature aerosols from biomass combustion, in which nucleation and condensation from fly ash forming vapors is controlled. The sampling method includes a high-temperature probe in which the hot gas is diluted and then cooled. Laboratory results from sampling a model aerosol with known concentrations of SiO 2 particles and KCl vapor showed that when using a high dilution ratio, the KCl vapor was effectively separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 11 publications
(10 reference statements)
3
38
1
Order By: Relevance
“…By using different dilution ratios and dilution gas temperatures, nucleation and condensation of inorganic vapors can be controlled. Either the vapor is guided to completely deposit in the probe, forced to condense on existing PM or form a distinct ultrafine mode that is clearly distinguishable from the original PM, as discussed more in detail by Strand et al [19]. Subsequently the tars can be removed prior to the actual PM measurements using e.g.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…By using different dilution ratios and dilution gas temperatures, nucleation and condensation of inorganic vapors can be controlled. Either the vapor is guided to completely deposit in the probe, forced to condense on existing PM or form a distinct ultrafine mode that is clearly distinguishable from the original PM, as discussed more in detail by Strand et al [19]. Subsequently the tars can be removed prior to the actual PM measurements using e.g.…”
Section: Introductionmentioning
confidence: 98%
“…The hot gas can also be diluted, e.g. by means of a dilution probe [16][17][18][19][20][21][22]. By using different dilution ratios and dilution gas temperatures, nucleation and condensation of inorganic vapors can be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Their condensation constitutes the main contributor to the fine ash fraction. Strand et al [282] identified two principal routes for condensation of these vapors into particles: a homogeneous nucleation where the vapor condenses into very fine droplets and agglomerates/accumulates into a particle and a heterogeneous condensation where the vapor on the surface of an existing particle entrains in the flue gas.…”
Section: Forms Of Mineral Matter In Solid Fuels and Influence On Ash mentioning
confidence: 99%
“…According to Strand et al (2004), the particle characteristics of the boiler flue gas are 1.2 × 10 7 particles/cm 3 n with a geometric mean diameter of 68 nm, consisting of K, S, and Cl.…”
Section: Commercial Biomass Combustion Exposurementioning
confidence: 99%